2017
DOI: 10.1515/sbe-2017-0008
|View full text |Cite
|
Sign up to set email alerts
|

A Review on the Evolution of Calendar Anomalies

Abstract: Abstract:In this article, we provide a detailed review on the behavior of calendar anomalies (dayof-the-week, January and turn-of-month

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 75 publications
0
4
0
Order By: Relevance
“…Other studies, such as Wong et al (2006), Abdul Karim et al (2012), Chia (2014), Olson et al (2015), Kumar (2017), Öztürk et al (2018), Shanaev and Ghimire (2021), concluded that anomalies decreased over time and that markets begin to become more efficient. Borges (2009) claimed that the anomaly was being affected by data mining bias and argued that there was variation in the national characteristics of different countries, which do not remain the same over time.…”
Section: Literature Reviewmentioning
confidence: 98%
See 1 more Smart Citation
“…Other studies, such as Wong et al (2006), Abdul Karim et al (2012), Chia (2014), Olson et al (2015), Kumar (2017), Öztürk et al (2018), Shanaev and Ghimire (2021), concluded that anomalies decreased over time and that markets begin to become more efficient. Borges (2009) claimed that the anomaly was being affected by data mining bias and argued that there was variation in the national characteristics of different countries, which do not remain the same over time.…”
Section: Literature Reviewmentioning
confidence: 98%
“…Borges (2009) claimed that the anomaly was being affected by data mining bias and argued that there was variation in the national characteristics of different countries, which do not remain the same over time. Kumar (2017) claimed that calendar anomalies were present during the 1980s and 1990s but have substantially decreased in recent times due to the significant advances in information technology which have reduced the cost of obtaining information. Also, over the examination period from 1926 to 2018, a recent study by Shanaev and Ghimire (2021) asserted that many calendar anomalies have disappeared.…”
Section: Literature Reviewmentioning
confidence: 99%
“…To gauge this leverage effect, Bollerslev (1986) suggested the GARCH model is another approach to estimate the market return. Several studies have been reviewed in Kumar (2017) and based on the findings, the markets have achieved a higher degree of efficiency during the 1980s and 1990s. Others related studies on calendar effect can be found in Abalala & Sollis 2015, Harshita & Yadav (2019) and Saldanha & Desai (2019).…”
Section: Introductionmentioning
confidence: 99%
“…However, the reality is that financial market exhibits certain anomalies in EMH – indicating prospects of predictability in asset price movements (see Roberts, 1959; Milonas, 1991; Brusa et al , 2000; Gunasekarage and Power, 2006). The voluminous literature of the EMH portrays that out of several anomalies, calendar anomalies have garnered substantial research attention because of their commonality and importance for investors and policymakers (see Kumar, 2017; Harshita et al , 2018; Plastun et al , 2019).…”
Section: Introductionmentioning
confidence: 99%